THE EFFECT OF GOVERNMENT SPENDING IN THE HEALTH, EDUCATION AND SOCIAL PROTECTION SECTORS ON INCOME INEQUALITY IN INDONESIA - Amanda Mahviza Harahap; Fanny Nailufar; Ichsan; Zata Hasyyati (LPPM Universitas Malikussaleh, 2026)
This study aims to examine the effect of government spending in the health, education, and social protection sectors on income inequality in Indonesia. The data used in this study are secondary data in the form of a time series from 2005 to 2024 obtained from the Central Bureau of Statistics. The data analysis method uses multiple linear regression. The results show that government spending in the health sector has a negative and significant effect on income inequality in Indonesia. Government spending in the education sector has a positive and significant effect on income inequality in Indonesia. Government spending in the social protection sector does not have a significant effect on income inequality in Indonesia. Simultaneously, government spending in the health, education, and social protection sectors has a positive and significant effect on income inequality in Indonesia.